(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The study of Dialects provides a great opportunity to consider not only the linguistic specifics of the people living only in a certain territory, but also the history of the language, kinship issues. Therefore, it can be said that the dialect means of one language are often not borrowed into the literary language of this people, but play a very important role in revealing the process of historical development of the national language of this people.This article discusses some of the phonetic features of the Aksy dialect.